Minimal Residual Disease in Multiple Myeloma: Current Landscape and Future Applications With Immunotherapeutic Approaches - Kostopoulos, Ioannis V.; Ntanasis-Stathopoulos, Ioannis; Gavriatopoulou, Maria; Tsitsilonis, Ourania E.; Terpos, Evangelos (Frontiers in Oncology, 2020)
The basic principle that deeper therapeutic responses lead to better clinical outcomes in cancer has resulted in technologies capable of detecting rare residual tumor cells. The need for ultra-sensitive approaches for minimal residual disease (MRD) detection is particularly evident in Multiple Myeloma (MM), where patients will ultimately relapse despite the achievement of complete remission, which is commonplace due to remarkable therapeutic advances. Consequently, current response criteria on MM have been amended based on MRD status and MRD negativity is now considered the most dominant prognostic factor and the most valuable indicator for a subsequent relapse. However, there are particular limitations and several aspects for MRD assessment that remain open. This review summarizes current data on MRD in the clinical management of MM, highlights open issues and discusses the challenges and the endless opportunities arising for both patients and clinicians. Furthermore, it focuses on the current status of MRD in clinical trials, its dynamics in addressing debatable aspects in the clinical handling and its potential role as the prevailing factor for future MRD-driven tailored therapies.